2022
DOI: 10.1093/jxb/erac328
|View full text |Cite
|
Sign up to set email alerts
|

The Sclerotinia sclerotiorum-inducible promoter pBnGH17 D7 in Brassica napus: isolation, characterization, and application in host-induced gene silencing

Abstract: Sclerotinia stem rot (SSR), caused by Sclerotinia sclerotiorum, is among the most devastating diseases in Brassica napus worldwide. Conventional breeding for SSR resistance in Brassica species is challenging due to the limited availability of resistant germplasm. Therefore, genetic engineering is an attractive means for developing SSR-resistant Brassica crops. Compared with constitutive promoter, S. sclerotiorum-inducible promoter would avoid ectopic expression of defense genes that may cause plant growth defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…For S. sclerotiorum inoculation in Arabidopsis, 4-week-old unfolded leaves were detached and placed on 2 mm in diameter mycelial agar plugs for leaf inoculation following the method outlined by Lin et al 57 . The inoculated leaves were photographed and quantified at 30 hpi.…”
Section: Assessment Of S Sclerotiorum Resistancementioning
confidence: 99%
“…For S. sclerotiorum inoculation in Arabidopsis, 4-week-old unfolded leaves were detached and placed on 2 mm in diameter mycelial agar plugs for leaf inoculation following the method outlined by Lin et al 57 . The inoculated leaves were photographed and quantified at 30 hpi.…”
Section: Assessment Of S Sclerotiorum Resistancementioning
confidence: 99%
“…The discovery of S. sclerotiorum-induced promoters is particularly important, and overexpression of resistance genes can enhance plant resistance and cause energy loss (Ding et al, 2021a). The promoter of glycosyl hydrolase 17 gene (pBnGH17) in rapeseed was shown to be induced by S. sclerotiorum; 5′-deletions and promoter activity analysis showed that a 189-bp region was essential for S. sclerotiorum to induce responses, and the promoter pBnGH17 D7 , which connects this region to the core promoter region, was induced after S. sclerotiorum infection, but it was less active under normal growth conditions (Lin et al, 2022). This provides an important reference for future work.…”
Section: Rapeseed Transgenic Strategymentioning
confidence: 99%
“…Yield penalty is a serious issue caused by the ectopic expression of defense-related genes, so an S. sclerotiorum-induced promoter needs to be developed. In this line, Lin et al (2022) developed pBnGH17 D7 which overcame this issue. It was also used for host-induced gene silencing control of the disease.…”
Section: Sclerotinia Stem Rotmentioning
confidence: 99%